2014
DOI: 10.1161/atvbaha.113.301925
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of an Inflammatory Disease

Abstract: This invited review summarizes work presented in the Russell Ross lecture delivered at the 2012 proceedings of the American Heart Association. We begin with a brief overview of the structural, cellular, and molecular biology of Krüppel-like factors. We then focus on discoveries over the past decade implicating Krüppel-like factors as key determinants of vascular cell function in atherosclerotic vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 113 publications
(131 reference statements)
0
22
0
Order By: Relevance
“…These data provide insights into a long-standing question in the field regarding redundancy between KLF2 and KLF4. Indeed, we and others have reported that both factors are induced by the same stimuli (e.g., flow and statins) and that both regulate similar key endothelial targets (e.g., Nos3 and Thbd) to confer antiinflammatory and antithrombotic effects to the vessel wall (4,6,9,16,26). Given the obvious requirement for an intact vasculature, it is likely that the redundancy of KLF2/4 provides an important safety net to ensure survival.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These data provide insights into a long-standing question in the field regarding redundancy between KLF2 and KLF4. Indeed, we and others have reported that both factors are induced by the same stimuli (e.g., flow and statins) and that both regulate similar key endothelial targets (e.g., Nos3 and Thbd) to confer antiinflammatory and antithrombotic effects to the vessel wall (4,6,9,16,26). Given the obvious requirement for an intact vasculature, it is likely that the redundancy of KLF2/4 provides an important safety net to ensure survival.…”
Section: Discussionmentioning
confidence: 89%
“…The endothelium is also a dynamic and highly responsive tissue whose function can be altered by biomechanical (e.g., blood flow) and biochemical (e.g., cytokine) stimuli (2). For example, laminar blood flow alters cellular gene expression in a manner that promotes a healthy endothelium and maintains vascular integrity while disturbed flow confers antiparallel effects (3,4). Further, biochemical stimuli, such as cytokines, can activate the endothelium, as seen in acute (e.g., sepsis) or chronic disease states (e.g., coronary artery disease), culminating in leakage of fluid from the intravascular space and tissue edema, formation of blood clots that impair flow, and altered vascular tone resulting in blood pressure dysregulation (2).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports identified KLFs as DNA-binding transcription factors that bind to GC-, GT-, and CACCC-box motifs in gene promoters and other regulatory elements in order to mediate gene expression. 17,2023 We therefore aimed to pinpoint the KLF recognition sites (GC-, GT-, and CACCC) of the HBA promoter that are critical for KLF2/KLF4 binding to augment the transactivation of the promoter in the endothelium. We first focused on four previously reported 4,5 KLF-binding sites of the HBA promoter (Figure 4A, site 1, −33 to −41 bp; site 2, −86 to −94 bp; site 3: −115 to −123 bp; site 4, −172 to −180 bp), which were mutated to prevent KLF-binding.…”
Section: Resultsmentioning
confidence: 99%
“…66 KLFs have potent effects on a broad range of vascular processes that contribute to atherogenesis, and all these experimental observations may lead to new clinical applications considering KLFs as therapeutic targets. 67 However, how endothelial cells adapt to flow changes in terms of maintenance of expression of specific arterial and venous properties remains to be defined in more detail both in healthy or pathological conditions. …”
Section: Discussionmentioning
confidence: 99%